An Epidemiological Study of Malnutrition and Its Associated Factors in School Going Adolescents of District Ghaziabad, Uttar Pradesh - Gunjan, Dr. Kumar; Arya, Dr. Vimal; Arya, Dr. R K (International Journal of Innovative Research in Medical Science, 2018)
Introduction: Today, the world faces double burden of malnutrition that includes both under nutrition and overweight, especially in developing countries. Malnutrition, especially in adolescent and young women, not only effects the growth and development in this generation but also in the next. This study has been designed with the objectives to assess the nutritional status and various socio-demographic variables in the adolescent population and their association with nutritional status of the adolescents in Ghaziabad, Uttar Pradesh. Material and Methods: The study was carried out during November 2013 to October 2014 in higher secondary schools in urban area of district Ghaziabad by Department of Community Medicine, Santosh Medical College, Ghaziabad. Multistage sampling technique was used. 50 subjects from each school were questioned with self-administered well-designed pre-tested and close-ended questionnaire. Data was coded and transferred to a master chart and simple and association tables were prepared and analysed with appropriate statistical tests like Chi-square test with Yates correction. Results: It was found that out of the total 550 adolescents, the majority of the adolescents (64%) were male while females added up to 36% of the total. The association between age and nutritional status of adolescents was statistically insignificant. The association between socio-economic status and nutritional status of adolescents was statistically insignificant.